english: - - Bernadinus Darma; Pius Weraman; Jacob M. Ratu (Syntax Corporation Indonesia, 2022)
East Nusa Tenggara (NTT) is still the third largest contributor to Malaria cases in Indonesia, with a prevalence of 12%, Papua (18.4%) and West Papua (26.1%). Directly border with The Democratic Republic of Timor Leste (RDTL) with Mota'ain as the main crossing point, increases the risk of infectious diseases transmission. Mota’ain is located in coastal areas, swamps, river basins, former fish ponds, and rice fields potentially to be Anopheles sp. habitats. The purpose of this research is to examine the characteristics and spatial distribution of potential breeding habitats for Anopheles sp. in Mota'ain. This is a descriptive analytic study with a cross-sectional design. The Anopheles sp mosquito bionomic area, which included swamps, rice fields, estuaries around the perimeter, and the buffer area of the Mota'ain border, served as the research sample. The spatial regression test was used to analyze the data, and the results revealed three points of Anopheles sp larvae habitats, namely fish ponds, swamps, and river basin. In the buffer area, 24 (80%) of the larvae habitats were found within a 200-meter radius, and 24 (80%) of the larvae habitats were found within a 400-meter radius 6 (20%). There was no habitat found around the perimeter. With a habitat index of 50%, the density of Anopheles sp larvae per catch ranged from 0.04 to 12.03. Anopheles sp larvae discovered included Anopheles Barbirostris, Anopheles Subpictus, and Anopheles Vagus. Swamps have the most habitat (3,004.7 m2), while river basins have the least (3,004.7 m2) (2.93 m2). The Spatial Regression Test revealed that habitat area (p = 0.014), water pH (p = 0.015), and salinity (p = 0.00012) were significant. This means that habitat area, water pH, and salinity all have an effect on Anopheles sp. density, whereas temperature has no effect (p = 0.778). Cleaning aquatic plants and employing larval predators to prevent larval breeding.